Cholera outbreak in a village in south India - Timely action saved lives - R. Deepthi; S.R. Sandeep; M. Rajini; H. Rajeshwari; Achal Shetty (Elsevier, 2013)
Summary: Cholera remains a public health concern in developing countries because of its high morbidity and mortality. This study was designed to assess the magnitude of and factors responsible for an outbreak in a South Indian village and to implement measures for containing and preventing the recurrence of such outbreaks. Data was obtained by surveying households in the village to identify cases and assess factors responsible for the outbreak. A sanitary survey of the water supply system was performed to identify the cause of the outbreak. Preventive measures were implemented by setting up a rapid response team to manage cases and provide safe drinking water and health education regarding the prevention of such outbreaks. A total of 73 cases were reported during the outbreak, an attack rate of 17.5%. Attack rates were similar among males and females, and the highest rates were observed among the elderly (33.3%), while the lowest rates were observed among adults (14.7%). There were no deaths reported due to cholera in the village. Most households (81%) surveyed did not use any method of water purification, 79.7% practiced open field defecation and 58.2% practiced inadequate hand washing, indicating poor sanitary practices. Cases were most commonly observed in houses which did not practice any method of water purification (p < 0.001) and among people living below the poverty line (p = 0.02). Despite the high attack rate, no deaths were reported, largely thanks to timely medical and preventive interventions. Keywords: Outbreak investigation, Cholera, Sanitary practices, Prevention